Strategi Aparat Desa dalam Penanganan Pengguna Narkoba di Desa Terantang Kecamatan Tambang Kabupaten Kampar Provinsi Riau - Efriani, Ressy; Jalil, Ashaluddin; Sidiq, Rd. Siti Sofro (Universitas Pahlawan Tuanku Tambusai, 2025)
This study reviews the strategy of Village Officials in handling drug users. This study uses a qualitative method, data collection is done by observation, interviews and documentation. The research subjects are five people who work at the Terantang Village Office. The purpose of this study is to determine the strategy of Village Officials in handling drug users.The results of this study indicate that the strategy often carried out by Village Officials in handling drug cases is a facilitative strategy, namely village officials often conduct socialization to the community regarding knowledge about drugs and the laws that ensnare drug users, village officials provide special complaint services if there is public suspicion of people involved in drugs and facilitate the community to exercise as a healthy lifestyle.